Unveiling the Jazz Age: A Critical Review of The Great Gatsby - Adhikari, Anup (International Research Journal of MMC, 2025)
This review article examines F. Scott Fitzgerald's "The Great Gatsby" as a critical insight into the American Dream during the Jazz Age. Employing a systematic approach, the review initially summarized each of the novel's nine chapters, tracing the unfolding plot and character arcs. Building upon this foundation, it conducts a literary analysis that probed into the novel's thematic richness, emphasizing Fitzgerald's pointed critique of materialism and the deceptive allure of the American Dream. The secondary data for this study was obtained from academically published, peer-reviewed journal articles, books, and reputable websites that analyze the aforementioned novel from different perspectives to support and critique this literary work. This analysis highlights Jay Gatsby's obsessive pursuit of wealth and social standing as a means to reclaim a past love, illustrating the dream's ultimately unattainable nature. Symbolic elements like the green light and the Valley of Ashes were explored to demonstrate their role in conveying the novel's central themes of aspiration and moral decay. Furthermore, the review interprets characters such as Tom and Daisy Buchanan, and Nick Carraway, as representative figures reflecting the social stratification and ethical ambiguities prevalent in 1920s American society. Ultimately, the review concludes that "The Great Gatsby" endured as a significant work of literature, providing a poignant social critique and a timeless reflection on the human condition, cautioning against the dangers of romanticizing the past and the superficiality inherent in a materialistic worldview. Hence, for implication, this study provides a nuanced understanding of The Great Gatsby as a literary reflection of the Jazz Age, offering valuable insights into the socio-cultural critique of the American Dream and its inherent moral contradictions, thereby enriching contemporary literary discourse on the interplay between aspiration and ethical decay.